RUSSIAN POPULATION OF THE NORTH CAUCASUS: SOCIOCULTURAL FEATURES IN THE VIEWS OF YOUNG PEOPLE - A. M. Erokhin; E. A. Avdeev; M. E. Erokhina (Современная наука и инновации, 2023)
The article, based on the sociocultural approach, analyzes the sociocultural features of the Russian population of the North Caucasus. Empirical data revealing the assessments and perceptions of Russian and North Caucasian youth were obtained in the course of a sociological study in 2022. The socio-cultural status of the North Caucasus Russian population is significantly affected by negative migration and demographic dynamics, which negatively affects the pace of socioeconomic development of the region. According to the study the sociocultural positions of the Russian population of the North Caucasus today are characterized as relatively stable. This is also confirmed by the prevailing attitudes among the polyethnic youth towards interethnic harmony and equality of the sociocultural status of all the North Caucasus peoples. The continued outflow of Russians from the North Caucasian regions is primarily due to socio-economic and demographic factors. The further stability of the socio-cultural positions of Russians directly depends on the pace of economic and socio-cultural development of the North Caucasus.